Respon Pemberian Asap Cair dan Zeolit Terhadap Pertumbuhan dan Hasil Tanaman Padi : Response of Liquid Smoke and Zeolite Administration to Growth and Yield of Rice Plants - Victor Bintang Panunggul (Agrifarm : Jurnal Ilmu Pertanian, 2022)
Natural fertilizer is one of the alternatives to support environmentally friendly food security programs and is expected to increase rice crop production. The purpose of this study is to determine the effect of liquid smoke and zeolite on the growth and yield of rice plants. The research was conducted in Pegalongan Village, Patikraja District, Banyumas Regency. The study has been carried out in April - July 2022. The study was studied using a Randomized Design Kelopok (RAK) factorial pattern consisting of two factors. The first factor consists of D0= control (no treatment), D1=10mL/L water per polybag, D2=20 mL/L water per polybag. While the second factor consists of Z0 = 0 kg/ha per polybag (without application), Z1 = 25 kg / ha, Z2 = 50 kg / ha. The results of liquid smoke on the growth variable had a marked-effect effect on the number of leaves at a dose of 20 mL of 20,21 clumps. Meanwhile, the variable observation of results has no real effect. The application of zeolite to plant growth had a significant effect on the observation of plant height and the number of saplings with a treatment of 50 kg / ha of 49,7 cm2 and 21,22 clumps. The application of zeolite has a noticeable effect on seed weight per plant and per effective with a treatment of 50 kg / ha of 7,16 g and 26,88 g.